Midgut and fat body: Multisystemic action of pyriproxyfen on non-target organism Ceraeochrysa claveri (Neuroptera: Chrysopidae) - Scudeler, Elton Luiz [UNESP]; Carvalho, Shelly Favorito de [UNESP]; Garcia, Ana Silvia Gimenes [UNESP]; Santorum, Marilucia [UNESP]; Padovani, Carlos Roberto [UNESP]; Santos, Daniela Carvalho dos [UNESP] (Elsevier, 2022)
Morphological tools can assist in the evaluation of effects of insecticides on non-target insects. Pyriproxyfen, a juvenile hormone analog, is known to interfere with growth and metamorphosis of insects. However, there are studies showing indirect effects on natural enemies, including green lacewings. Few prior studies describe morphological effects of pyriproxyfen on target insect organs, especially on natural enemies. Through morphological tools, this study aimed to characterize the midgut and fat body, both important organs of digestion and great metabolic activity respectively, of the predator Ceraeochrysa claveri after chronic exposure to pyriproxyfen. Larvae of C. claveri were fed Diatraea saccharalis egg clusters treated with pyriproxyfen in solution of 50 or 100 mg a.i. L−1 throughout the larval stage. The biological data revealed significant increases in development time, especially in the third instar, and in cumulative mortality from the prepupal into the pupal stage. Morphological analysis of adult midgut (≤24 h old) showed damage including formation of epithelial folds, intercellular spaces, emission of cytoplasmic protrusions. Both fat body regions presented decrease of lipid droplets, vacuolization of trophocytes and mitochondrial injury featuring a multisystemic action. In both organs, pyriproxyfen exposure induced significant oxidative stress by mitochondrial superoxide production. Cytoprotective responses were induced in midgut and fat body cells by augmenting the number of cytoplasmic granules containing calcium and expression of HSP 90. Both organs proved to be efficient in presenting histopathological alterations, showing the sensitivity and applicability of this morphological tool for evaluating other insecticides in non-target organisms.
Keywords: Cytotoxicity; Insect; Insecticide; Lacewings; Morphology; Predator